PENGEMBANGAN SOAL TES HOTS BERBASIS KAHOOT PADA MATERI SAUCE UNTUK SISWA SMK KULINER DI SMKN 1 BUDURAN - Ferninda Adelia Bayu Samudra; Lucia Tri Pangesthi; Mauren Gita Miranti; Ita Fatkhur Romadhoni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the quality of Kahoot-based Higher Order Thinking Skills (HOTS) test questions on Sauce material, and the development results in terms of validity, reliability, difficulty level, discriminating power, and distractor effectiveness. This research employed the Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate). The developed product consisted of 50 multiple-choice HOTS questions covering cognitive levels C4 (14 items), C5 (27 items), and C6 (9 items), delivered through the Kahoot application to tenth-grade Culinary students at SMKN 1 Buduran. Validation by three judgment experts yielded an overall average score of 89.70%, categorised as Very Feasible, comprising content (89.58%), construction (88.96%), and language (90.56%) aspects. Item analysis involving 31 students revealed 31 valid items (62%) and 19 invalid items (38%). The reliability of the valid items reached a Cronbach's Alpha of 0.88, classified as Very High. Discriminating power results showed 1 item as very good, 20 good, 7 fair, and 3 poor. Difficulty levels comprised 16 easy items, 9 moderate items, and 6 difficult items. Distractor effectiveness reached 99.98%, distributed across very good (19.35%), good (35.48%), fair (29.03%), poor (12.90%), and very poor (3.22%) categories. These findings indicate that the Kahoot-based HOTS test instrument on Sauce material is valid, reliable, and feasible to be used as an evaluation tool in vocational culinary education.